Swimming performance following different recovery protocols - Felix, S. D. (1996)
The study was to designed compare lactate levels and subsequent swimming performance following a maximal swim using three different recovery protocols: swimming; rowing; and passive rest. Participants from the Springfield College swim team (N is 10) were tested under each recovery protocol. Experimental sessions were separated by at least one day. Each session consisted of two 200-yd freestyle swims, separated by 14 min of recovery. The 14-min recovery period was broken into three sections: 2 min to prepare for the recovery; 10 min of recovery; and 2 min to prepare for the second trial swim. Variables measured were blood lactate concentrations across time and the time difference between trial swims. Blood was taken at rest and at 2, 7, and 12 min during the recovery period. A 3 x 4 repeated measures ANOVA was used to analyze the difference in lactate levels across recovery protocols and across time. A one-way repeated measures ANOVA was used to analyze time differences between the two trials across the three recovery protocols. A significantly (p<.05) lower mean time difference and mean lactate levels for swimming recovery was found as compared to the mean time difference and mean lactate levels for passive rest recovery. No difference (p>.05) was found between swimming and rowing recovery protocols for mean lactate levels and mean time difference between trials. Swimming recovery resulted in less of a decrement in subsequent swimming performance than passive rest, possibly as a result of enhanced lactate removal.